Socio-demographic and clinical profile of hypertensive patients accompanied by the Family Health Strategy - Natan David Pereira; Thamires Fernandes Cardoso da Silva Rodrigues; Rafaely de Cassia Nogueira Sanches; Marcia Glaciela da Cruz Scardoelli; Fernanda Gatez Trevisan; Anderson da Silva Rêgo; Cremilde Aparecida Trindade Radovanovic (O Mundo da Saúde, 2018)
Hypertension is a disease of high prevalence, affecting about seven million people in the world. The knowledge of risk factors, such as anthropometric, socioeconomic and health profiles, allows programming interventionist measures in health promotion. Therefore, this study aimed to characterize the sociodemographic and clinical profile of people with arterial hypertension, accompanied by the Family Health Strategy in a municipality in the northwest of the state of Paraná. A cross-sectional study was carried out with 417 people from February to June 2016. Data were collected applying a user satisfaction instrument of the services provided by Primary Care, using the variables related to the sociodemographic and clinical profile of the interviewees. For the treatment of variables, descriptive statistics were used. Of the participants, 62.4% were elderly, of which 31.9% were over 70 years old, 68% were female, with incomplete elementary education and belonging to economic classes C1, C2 and DE. Of those interviewed, 39.8% were classified as having an overweight body mass index, 35.7% were obese and 68.8% had an abdominal circumference above the recommended parameters. Although blood pressure was not statistically significant, most users had some degree of change in systolic and diastolic blood pressure levels. These findings contribute to subsidize the planning of actions that meet the demands of the population assisted.